Systematic review and meta-analysis shows a specific micronutrient profile in people with Down Syndrome: Lower blood calcium, selenium and zinc, higher red blood cell copper and zinc, and higher salivary calcium and sodium. - Amene Saghazadeh; Maryam Mahmoudi; Atefeh Dehghani Ashkezari; Nooshin Oliaie Rezaie; Nima Rezaei (PLoS ONE)
Different metabolic profiles as well as comorbidities are common in people with Down Syndrome (DS). Therefore it is relevant to know whether micronutrient levels in people with DS are also different. This systematic review was designed to review the literature on micronutrient levels in people with DS compared to age and sex-matched controls without DS. We identified sixty nine studies from January 1967 to April 2016 through main electronic medical databases PubMed, Scopus, and Web of knowledge. We carried out meta-analysis of the data on four essential trace elements (Cu, Fe, Se, and Zn), six minerals (Ca, Cl, K, Mg, Na, and P), and five vitamins (vitamin A, B9, B12, D, and E). People with DS showed lower blood levels of Ca (standard mean difference (SMD) = -0.63; 95% confidence interval (CI): -1.16 to -0.09), Se (SMD = -0.99; 95% CI: -1.55 to -0.43), and Zn (SMD = -1.30; 95% CI: -1.75 to -0.84), while red cell levels of Zn (SMD = 1.88; 95% CI: 0.48 to 3.28) and Cu (SMD = 2.77; 95% CI: 1.96 to 3.57) were higher. They had also higher salivary levels of Ca (SMD = 0.85; 95% CI: 0.38 to 1.33) and Na (SMD = 1.04; 95% CI: 0.39 to 1.69). Our findings that micronutrient levels are different in people with DS raise the question whether these differences are related to the different metabolic profiles, the common comorbidities or merely reflect DS.